Microstructured SHG patterns on Sm2O3-doped borophosphate niobium glasses by laser-induced thermal poling. Issue 7 (1st April 2021) - He, Xiaoyan; Hu, Daming; Yang, Guang; Adamietz, Frederic; Rodriguez, Vincent; Dussauze, Marc; Fargues, Alexandre; Fargin, Evelyne; Cardinal, Thierry
Abstract: A microstructured SHG pattern on Sm2 O3 -doped sodium borophosphate niobium (SmBPN) glasses was obtained by laser-induced thermal poling. The optical properties of SmBPN glasses were recorded by UV/Vis/NIR transmission spectra. In situ laser-induced heating of the SmBPN glasses without and with preheating was characterized by an infrared thermal camera. A laser-induced microstructured pattern was written on the ITO electrode, resulting in a local electric field enhancement during the poling process. Laser-induced heating together with the enhanced local electric field of the microstructured electrode governed the geometry and strength of the electrical field of these SmBPN glasses. This poling process could be a potential method to design second-order optical properties or even to fabricate microstructures.